The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1111/eje.12090
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of training senior dental students on oral health care for disabled patients

Abstract: Our findings indicate that a short-term training programme on oral health care has an immense impact on students' adherence to treating disabled patients. These results provide evidence to support the necessity of enrichment of the dental curriculum regarding oral health care for disabled patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(40 citation statements)
references
References 19 publications
1
33
0
Order By: Relevance
“…Results using various other measures in longitudinal studies are mixed. Whilst older studies showed a failure of curricula to improve attitudes amongst dental students , a number of other studies show effectiveness . Considering attitude change, effective curricula may involve a diverse range of teaching methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Results using various other measures in longitudinal studies are mixed. Whilst older studies showed a failure of curricula to improve attitudes amongst dental students , a number of other studies show effectiveness . Considering attitude change, effective curricula may involve a diverse range of teaching methods.…”
Section: Discussionmentioning
confidence: 99%
“…Considering attitude change, effective curricula may involve a diverse range of teaching methods. Examples include a 1‐year clinical and didactic curriculum for dental hygiene students , a short lecture series augmented with case presentations for fourth year dental students , and a mixture of lectures, group discussion, screening and fluoride varnish provision for patients with disabilities .…”
Section: Discussionmentioning
confidence: 99%
“…Information was designed to be anonymous. Items were derived from variables suggested as important by the literature . Items included sex, year of birth, geographical family background (rural, urban etc.…”
Section: Methodsmentioning
confidence: 99%
“…Items were derived from variables suggested as important by the literature. [7][8][9][10][11]24,25,27 Items included sex, year of birth, geographical family background (rural, urban etc. ); socioprofessional status of mother and father; principal source of finance during studies; lived environment whilst a student; direct personal experience or experience of working with, or socialising with, people with disability or in marginalised groups; membership of charitable or community organisations; and stage in dental training or years of experience in practice.…”
Section: Development Of a Battery Of Adapted And New Scales (Draft 1)mentioning
confidence: 99%
See 1 more Smart Citation